2006
DOI: 10.1080/01443610600555295
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of clinical pregnancies after ovulation induction using metformin

Abstract: The objective of this study was to review the first 50 clinical pregnancies of women with polycystic ovarian syndrome (PCOS) who had ovulation induced either with metformin alone, or in combination with clomifene. The study was confined to women with PCOS attending our infertility service. A register of clinical pregnancies was maintained of women who conceived after metformin therapy. The metformin was continued throughout the first trimester. The outcome of pregnancy was determined by individual chart review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…plasma endothelin-1, soluble intercellular adhesion molecule, soluble vascular adhesion molecule and E-selectin [36][37][38][39]). But safety always comes first and in a recent study Turner and associates [40] found there was no evidence of any adverse clinical effects when metformin is continued in the first trimester following ovulation induction in PCOS women. There was also no evidence of an increase in the rate of miscarriage or multiple pregnancies.…”
Section: Discussionmentioning
confidence: 96%
“…plasma endothelin-1, soluble intercellular adhesion molecule, soluble vascular adhesion molecule and E-selectin [36][37][38][39]). But safety always comes first and in a recent study Turner and associates [40] found there was no evidence of any adverse clinical effects when metformin is continued in the first trimester following ovulation induction in PCOS women. There was also no evidence of an increase in the rate of miscarriage or multiple pregnancies.…”
Section: Discussionmentioning
confidence: 96%
“…This is gradually increased over a three-week period from 500 mg once a day to 500 mg three times a day to reduce gastrointestinal side effects [16]. If the woman does not conceive after four months of metformin treatment, clomifene citrate (Clomid) is added at 50 mg daily orally from day 2-6 of the menstrual cycle.…”
Section: Methodsmentioning
confidence: 98%
“…Of the 25 trials included for this review, there were four randomised controlled trials (RCTs) [10][11][12][13], one clinical trial [14], four retrospective cohort studies [15][16][17][18], and sixteen prospective cohort studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. These studies were conducted globally with a large number originating from USA.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were conducted globally with a large number originating from USA. Metformin was limited to the first trimester in four trials [11,14,16,27], with the remainder continuing metformin for the entire duration of pregnancy. A comparison of continuing metformin in the first trimester and throughout pregnancy was made in four trials [10,23,26,33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation